Floodplain Trapping and Cycling Compared to Streambank Erosion of Sediment and Nutrients in an Agricultural Watershed1. (22nd January 2018) - Gillespie, Jaimie L.; Noe, Gregory B.; Hupp, Cliff R.; Gellis, Allen C.; Schenk, Edward R.
Abstract: Floodplains and streambanks can positively and negatively influence downstream water quality through interacting geomorphic and biogeochemical processes. Few studies have measured those processes in agricultural watersheds. We measured inputs (floodplain sedimentation and dissolved inorganic loading), cycling (floodplain soil nitrogen [N] and phosphorus [P] mineralization), and losses (bank erosion) of sediment, N, and P longitudinally in stream reaches of Smith Creek, an agricultural watershed in the Valley and Ridge physiographic province. All study reaches were net depositional (floodplain deposition > bank erosion), had high N and P sedimentation and loading rates to the floodplain, high soil concentrations of N and P, and high rates of floodplain soil N and P mineralization. High sediment, N, and P inputs to floodplains are attributed to agricultural activity in the region. Rates of P mineralization were much greater than those measured in other studies of nontidal floodplains that used the same method. Floodplain connectivity and sediment deposition decreased longitudinally, contrary to patterns in most watersheds. The net trapping function of Smith Creek floodplains indicates a benefit to water quality. Further research is needed to determine if future decreases in floodplain deposition, continued bank erosion, and the potential for nitrate leaching from nutrient‐enriched floodplain soils could pose a long‐term source of sediment and nutrients to downstream rivers.